Transformation of culture and political participation in Iran's civil society during the years 1384-1357 (Scientific Journal of Research Studies in Future Human Sciences, 2024)
Political culture is undoubtedly one of the factors in the formation and development of civil society, and as an independent variable, it has a fundamental effect on the citizens' familiarity with their rights. be discussed. The culture of any society is effective in drawing the structure of that society; So that political culture theorists, such as Almond and Powell, have used the division of political culture of different societies to divide their political systems. Meanwhile, many factors are effective in the progress of societies; Including the political culture of the society, which is one of the important factors that can cause the development or non-development of the civil society, in this thesis, it has been tried to analyze this important to reveal the weaknesses and obstacles on the way of the civil society. In this work, the researcher sought the transformation of culture and political participation in Iran's civil society during the years 1384-1357. And it was concluded that political culture has caused the process of political socialization to become more widespread in Iran from 1957 to 1984, and people, while getting to know the system through obtaining information, realize their responsibilities, rights and roles in the society.